2008
DOI: 10.1016/j.nurt.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic Dystrophy: Therapeutic Strategies for the Future

Abstract: Summary: Myotonic dystrophy (DM) is a dominantly inherited neurodegenerative disorder for which there is no cure or effective treatment. Investigation of DM pathogenesis has identified a novel disease mechanism that requires development of innovative therapeutic strategies. It is now clear that DM is not caused by expression of a mutant protein. Instead, DM is the first recognized example of an RNA-mediated disease. Expression of the mutated gene gives rise to an expanded repeat RNA that is directly toxic to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 71 publications
0
24
0
4
Order By: Relevance
“…The presence of the mutated gene produces an expanded repeat RNA that is highly noxious to cells. The mutant RNA is accumulated in the nucleus compartment, originating ribonuclear clusters in pathological tissue [19] . There are two types of DM caused by microsatellite expansions in two different genes.…”
Section: Outline Of Plcβ1 Targets and Pathologymentioning
confidence: 99%
“…The presence of the mutated gene produces an expanded repeat RNA that is highly noxious to cells. The mutant RNA is accumulated in the nucleus compartment, originating ribonuclear clusters in pathological tissue [19] . There are two types of DM caused by microsatellite expansions in two different genes.…”
Section: Outline Of Plcβ1 Targets and Pathologymentioning
confidence: 99%
“…B. mit Tolperison, Methocarbamol, Gabapentin, Pregabalin, L-Dopa, Azetazolamid, Amytryptilin, Mirtazapin oder Citalopram erfolgreich behandelt. Opiate und nichtopiathaltige Schmerzmittel sowie Antiphlogistika sind meist unwirksam [13,14,15,16,19]. Systematische Studien fehlen.…”
Section: Vorsorgeuntersuchungen Und Symptomatische Therapieunclassified
“…Recently, several gene therapy protocols, based on inhibitory RNA or short oligonucleotides that target the toxic mDMPK transcript, have been described for DM1 therapy (Wheeler, 2008). For the successful application of the RNA-or oligonucleotide-mediated strategies to clinical DM1 treatment, specificity, safety, and efficacy, in addition to delivery issues, are important criteria to be considered.…”
Section: Ribozyme-accessible Uridines In Mdmpk 3'-utr Rnamentioning
confidence: 99%
“…Another developed ribozyme that targets downstream of the expanded CUG repeats (Rib 854) could be useful to replace the toxic RNA that is entrapped in the nucleus with RNA that can be released into the cytoplasm. Recent findings showed that mDMPK 3'-UTR that is aberrantly retained in the nucleus could be transported extensively to the cytoplasm when it has attached to its 3'-end the woodchuck posttranscriptional regulatory element (WPRE), which can naturally accumulate hepatitis transcripts in the cytoplasm, resulting in an increase in myoblast differentiation whose initiation is failed in mutant 3'-UTR-expressing cells (Mastroyiannopoulos et al, 2005 and2008).…”
Section: Ribozyme-accessible Uridines In Mdmpk 3'-utr Rnamentioning
confidence: 99%
See 1 more Smart Citation